Ethnomathematical Exploration on Malaysian Malay Songket Cloth - Andhany, Ella; Lubis, Nurainun; Rambe, Ahmadsyah Fauzian (MaPan : Jurnal Matematika dan Pembelajaran, 2025)
Ethnomathematics serves as a bridge between formal mathematics and local culture, thereby helping students connect mathematics with real-life situations. This study focuses on revealing ethnomathematical concepts found in Malaysian Malay songket cloth that are not limited to geometric elements. Therefore, this research aims to explore the ethnomathematics embedded in Malaysian Malay songket fabric. The research was conducted in Kuala Lumpur, Malaysia, specifically at souvenir markets on Jalan Masjid India, the World Malay Ethnology Museum, the Orang Asli Arts and Crafts Museum, and the National Textile Museum. Data collection techniques included interviews with songket sellers and museum staff, observations, and documentation using observation and documentation sheets. The study employed a qualitative research method with an ethnographic approach, and data analysis was carried out using the Miles and Huberman model. The results show that Malaysian Malay songket cloth, which consists of six patterns, contains ethnomathematical elements. These include the hierarchical meaning in the cloth-making process, which aligns with the hierarchy of material in mathematics learning. Furthermore, Malay cakes reflect the application of function concepts and the determination of coordinate points, while the patterns and motifs of the cloth contain various geometric shapes (parallelograms, rectangles, squares, and triangles), line concepts, number patterns, and reflection concepts. The implication of this study is that the findings can serve as an alternative source of contextual and meaningful mathematics learning that is closely related to students’ everyday lives. Abstrak: Etnomatematika menjadi jembatan antara matematika formal dan budaya lokal, sehingga membantu siswa mengaitkan matematika dengan kehidupan nyata. Penelitian ini berfokus pada pengungkapan konsep etnomatematika dalam kain songket Melayu Malaysia yang tidak hanya terbatas pada unsur geometri. Sehingga penelitian ini bertujuan untuk mengeksplorasi etnomatematika yang terdapat pada kain songket Melayu Malaysia. Penelitian berlokasi di Kuala Lumpur, Malaysia yaitu pasar penjualan souvenir di Jalan Masjid India Muzium Etnologi Dunia Melayu dan Muzium Seni Kraf Orang Asli, dan Muzium Textile Nasional. Teknik pengumpulan data yaitu wawancara terhadap penjual songket serta petugas musium, observasi dan dokumentasi menggunakan Lembar Observasi dan Dokumentasi. Metode yang digunakan adalah metode penelitian kualitatif dengan pendekatan etnografi. Teknik pengumpulan data yaitu wawancara terhadap penjual songket serta petugas musium, observasi dan dokumentasi menggunakan lembar observasi dan dokumentasi. Teknis analisis data menggunakan Miles dan Huberman. Hasil penelitian ini menemukan bahwa kain songket Melayu Malaysia yang terdiri dari 6 corak mengandung etnomatematika, seperti pada pembuatan kain yang mengandung makna hirarki proses yang selaras dengan hirarki materi dalam pembelajaran matematika. Kemudian, Kek Melayu mengandung penerapan konsep fungsi dan penentuan koordinat titik, serta pola dan motif kain mengandung beberapa bentuk geometri (yaitu jajargenjang, persegi panjang, persegi, segitiga), konsep garis, konsep pola bilangan, serta konsep refleksi. Adapun implikasi penelitian ini adalah hasil temuan dapat menjadi alternatif sumber belajar matematika yang konstekstual, bermakna dan dekat dengan kehidupan siswa.